HISTORICAL DEVELOPMENT AND CONSTITUENT ELEMENTS OF MUQARNAS IN THE ISLAMIC WORLD - Shakhboz Mustafoev (International Journal of Innovations in Engineering Research and Technology, 2021)
The main goal of the article is to reveal the etymological meanings of muqarnas, place of origin, original types of stalactites, structural elements and evolutionary development. The article also discusses the first types of stalactites.